Principles of protein targeting to the nucleolus - Martin, Robert M. (2021)
© 2015 The Author(s). Published with license by Taylor & Francis Group, LLC© Robert M Martin, Gohar Ter-Avetisyan, Henry D Herce, Anne K Ludwig, Gisela Lättig-Tünnemann, and M Cristina Cardoso This is an Open Access article distributed under the terms of the Creative Commons Attribution-Non-Commercial License (http://creativecommons.org/licenses/by-nc/3.0/), which permits unrestricted non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited. The moral rights of the named author(s) have been asserted.